Концепции языка как мироотношенческие модели - Гусева, Н. В. (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статье представлен философский анализ концепций языка в качестве мироотношенческих моделей, его осмысление с точки зрения различной «предметной» направленности, в рамках исторически обусловленных, смысловых «систем координат», формирующих определенный тип понимания языка, воспроизводящий в то же время существенные черты культуры соответствующего периода.This paper presents a philosophical analysis of the concept of language as a model outlook, understanding language in terms of different «subject» orientation, within the historically conditioned, meaning «coordinate system», which form some type of understanding of the language that plays at the same time the essential features of the respective culture period. The author has reproduced the logic of conceptual examination of language in historical and philosophical progress, address a number of contemporary philosophical theories concerning language. It appears a prerequisite for proper human relationship to the world. Knowledge of this condition can not be meaningfully important to address any issues that characterize the current relationship of man with the world. Different understanding of language as a condition of the human connection to the world involves awareness of the possibility of the presence of different specificity patterns, forms of exercise, how to play so that significantly adjust image of the world in which a person performs its vital functions. Activity-conception of man and society methodologically adequate causes for unity reflection phenomena of human existence as its own cultural and civilizational phenomena of nature, opposing each other on the principles of their formation. In the context of consumerism for the world culture as a means of creative, socially meaningful relationship between man and the world does not appear. Just as it does not manifest itself as a cultural phenomenon.
Concept of Language as an Outlook Model.
Keywords: язык; language; мироотношение; outlook; слово; word; знак; sign; знаковая система; sign system